Dynamics of professional burnout - a comparative analysis considering the selected sectors in Poland, part II - Witkowski, Stanisław A.; Ślazyk-Sobol, Magdalena (Management (Zielona Góra), 2013)
Dynamics of professional burnout - a comparative analysis considering the key sectors in Poland, part II The article is a continuation of the study presented in the text entitled: „Professional burnout - a comparative analysis considering the selected sectors in Poland”. Management. University of Zielona Góra, Faculty of Economics and Management, Vol. 16, No.2., (p. 87 - 102). The authors present the results of the second part of the research on analysing the phenomenon of burnout among employees of the major sectors in Poland. The present material relates to the results of the re-test conducted after the nine-month interval. One again the cause-effect dependency models for the verified variables were presented for all the tested employed people and separately for each of the specified sectors. The most relevant applicable conclusions resulted from the implemented research projected were formulated. Dynamika wypalenia zawodowego - analiza porównawcza z uwzględnieniem głównych branż w Polsce, część II Artykuł stanowi kontynuację pracy przedstawionej w tekście „Professional burnout - a comparative analysis considering the selected sectors in Poland”. Management. Universtity of Zielona Góra, Faculty of Economics and Management, Vol. 16, No.2., (p. 87 - 102). Autorzy prezentują wyniki drugiej części badań poświęconych analizie zjawiska wypalenia wśród pracowników głównych branż w Polsce. Niniejszy materiał dotyczy wyników retestu, zrealizowanego po dziewięciomiesięcznej przerwie. Ponownie przedstawiono modele zależności przyczynowo - skutkowych dla weryfi kowanych zmiennych w odniesieniu do wszystkich badanych pracowników a także oddzielnie dla każdej z opisywanych branż. Sformułowano także najważniejsze wnioski aplikacyjne wynikające ze zrealizowanego projektu badawczego.